The Relationship of Psychological Well-being with a Cardiac Diet Self Efficacy in Acute Coronary Syndrome Patients - Ismail Fahmi; Ade Suryaman; Mashudi Mashudi; Amelia Ganefianty (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2022)
ABSTRACTIntroduction: Acute Coronary Syndrome (ACS) is a cardiovascular disease that causes significant deaths in most countries. No study assessed directly how this psychological well-being is related to Cardiac Diet Self-Efficacy (CDSE). Purpose: This study aimed to identify the relationship between psychological well-being and cardiac diet self-efficacy in ACS patients after treatment.  Method: This cross-sectional study involved 150 patients at two hospitals in Jambi Province that treated heart disease, especially ACS. We used Cardiac Diet Self-Efficacy (CDSE) Scale and Psychological Well-Being questionnaire. The associations between psychological well-being a cardiac diet self-efficacy were confirmed by the Pearson Correlation test using SPSS 26.0. Results: The correlation test showed a p-value of 0.018, indicating a relationship between psychological well-being and cardiac diet self-efficacy. Furthermore, the value of r obtained at 0.41 shows a reasonably strong relationship between psychological well-being and cardiac diet self-efficacy. Conclusion: Therefore, it is necessary to prepare for improving psychological well-being in ACS patients both from the discharge planning stage and post-hospital intervention so that ACS patients can have good cardiac diet self-efficacy after treatment.ABSTRAKLatar belakang: Sindrom Koroner Akut (SKA) adalah penyakit kardiovaskular yang menyebabkan kematian signifikan di sebagian besar negara. Tidak ada penelitian yang menilai secara langsung bagaimana psychological well-being ini terkait dengan Cardiac Diet Self-Efficacy (CDSE). Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara psychological well-being dengan cardiac diet self-efficacy pada pasien syndrome coroner akut (SKA) pasca pengobatan. Metode: Studi potong lintang ini melibatkan 150 pasien di dua rumah sakit di Provinsi Jambi yang melayani pengobatan penyakit jantung khususnya penyakit ACS. Kami menggunakan skala Cardiac Diet Self-Efficacy (CDSE) dan kuesioner Psychological Well-Being. Hubungan antara psychological well-being dengan cardiac diet self-efficacy dikonfirmasi oleh uji Korelasi Pearson menggunakan SPSS 26.0. Hasil: Uji korelasi menunjukkan nilai p 0,018, yang menunjukkan hubungan antara psychological well-being dengan cardiac diet self-efficacy. Selanjutnya, nilai r yang diperoleh sebesar 0,41 menunjukkan hubungan yang cukup kuat antara psychological well-being dengan cardiac diet self-efficacy. Simpulan: Oleh karena itu, perlu dilakukan persiapan untuk peningkatan psychological well-being pada pasien SKA baik dari tahap discharge planning maupun intervensi pasca perawatan rumah sakit agar pasien SKA dapat memiliki cardiac diet self-efficacy yang baik setelah dilakukan perawatan.